Violência no trabalho da enfermagem em um serviço de hemodiálise - Cordenuzzi, Onélia da Costa Pedro (2011)
Violence in the work environment is growing; being nursing is one of the professions in health more likely to suffer it. Throughout this research, it was chosen to investigate violence in the work of nursing in hemodialysis service. The objectives of this study consisted in identifying the determinants of violence at work recognized by the nursing staff of hemodialysis service and know the strategies adopted concerning the issue. It is a qualitative research which had as study environment a service of hemodialysis. Inclusion criteria were: being a nurse, technician or auxiliary nurse, to be a current employee and be working at the period of data collection. The focus group technique was chosen to obtain the data, which occurred in June 2010, according to the ethical guidelines for research involving humans. The data were treated according to theme analysis, being organized and discussed through three theme lines: the understanding given to violence in work environment, workplace violence in the space of chronic kidney disease when the patient is the assailant and, finally, the strategies used by nursing staff to face violence at work in the service of hemodialysis. Eight nursing staff participated in the study. It was highlighted that the concept of workplace violence is complex, depending on individual conceptions of each worker. Violence was described as quotidian in the context of chronic illnesses, being the verbal form the main one in these environments. The patient on hemodialysis was highlighted as the main agent of violence in this context, being influenced by chronic disease status of relations with the nursing staff, due to personal characteristics of the patient and, finally, as a matter of everyday life. Participants stated that violence causes pain and illness in the team, adopting the following strategies: tolerance for violence by the health condition of the patient; giving in not to be attacked, take a strong position and get away from the offender patient. It can be said that violence in nursing work is present in hemodialysis services studied and, with this study, awoke to taking actions that seek ways to face this reality. In this sense, it is understood that these results should not be taken as absolute and direct to the paths that can be investigated, recommending the expansion of the discussions about violence at work in other hemodialysis services.